OS BENS DE GIFFEN - SILVA, PALOMA E. Z.; BRUM, ARGEMIRO L.; FILHO, MAURÍCIO C.; RI, MARLENE D.; PETRY, DÉBORA; JOHANN, DENISE; BRAUN, FELIPE; KUNZ, JULIANE; ZINGLER, KARINE; SOUZA, JOSÉ D. D. S. (Salão do Conhecimento, 2013)
Resumo